2004
DOI: 10.1037/0022-0663.96.3.424
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Imagined Activity Can Enhance Young Children's Reading Comprehension.

Abstract: The Indexical Hypothesis suggests a new method for enhancing children's reading comprehension. Young readers may not consistently "index," or map, words to the objects the words represent. Consequently, these readers fail to derive much meaning from the text. The instructional method involves manipulating toy objects referred to in the text (e.g., a barn, a tractor, a horse, in a text about a farm) to simulate the actions described in the text. Correctly manipulating the objects forces indexing and facilitates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
202
4
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(242 citation statements)
references
References 48 publications
(64 reference statements)
16
202
4
7
Order By: Relevance
“…Accumulating evidence from embodied cognition research supports the argument that action enhances comprehension (Asher 1977;Glenberg and Goldberg 2011;Glenberg et al 2004;Tellier 2008). In recent years, the findings obtained from brain research also echo the view that language processing is an embodied process (Aziz-Zadeh and Damasio 2008; Willems and Casasanto 2011); that bodily action in the contextual environment and the person's perceptual experiences are inseparable during the cognition process.…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…Accumulating evidence from embodied cognition research supports the argument that action enhances comprehension (Asher 1977;Glenberg and Goldberg 2011;Glenberg et al 2004;Tellier 2008). In recent years, the findings obtained from brain research also echo the view that language processing is an embodied process (Aziz-Zadeh and Damasio 2008; Willems and Casasanto 2011); that bodily action in the contextual environment and the person's perceptual experiences are inseparable during the cognition process.…”
Section: Introductionsupporting
confidence: 48%
“…Studies in line with embodied cognition have observed different roles of actions in cognitive processes and have suggested that human mind is closely connected to sensorimotor experience. Several general theories of embodied cognition, such as those proposed by Glenberg et al (Glenberg et al 2004;Glenberg and Goldberg 2011;Glenberg and Kaschak 2002) and Barsalou (2008) argued that the cognitive process develops when a tightly coupled system emerges from interactions between organisms and their environment, with the interactions being real-time and goal-directed (Cowart 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when speakers are asked to use their hands to act out an event conveyed in a sentence, their memory for the event is better than if they merely read the sentence or translate it into another spoken language (Cohen, 1981;von Essen & Nilsson, 2003). Similarly, children understand stories better when they enact the story with objects or imagine enacting the story with objects than when they read the story twice (Glenberg, Gutierrez, Levin, Japuntich, & Kaschak, 2004), and actors recall the lines they produce while moving better than the lines they produce while standing still (Noice & Noice, 1999). …”
Section: How Does Gesture Lead To Learning That Lasts?mentioning
confidence: 99%
“…For example, when children manipulated objects and performed actions referred to in text using physical objects, their reading comprehension improved (Glenberg, Guitierrez, Levin, Japuntich, & Kaschak, 2004). Contextualizing abstract problems in personally relevant or interesting situations (such as familiar schemas: Nisbett & Ross, 1980;Wason & Shapiro, 1971; or fantasy situations: Parker & Lepper, 1992) has also produced learning benefits.…”
mentioning
confidence: 99%